Financial Distress, Regional Independence and Corruption: An Empirical Study in Indonesian Local Governments - Evi Maria; Abdul Halim; Eko Suwardi (JASF: Journal of Accounting and Strategic Finance, 2021)
This study aims to determine the effect of financial distress and regional independence on the probability of corruption in the local governments, of Indonesia. This study used panel data from local governments in Indonesia in 2012 and 2013 with 785 local governments. Data in 2012 and 2013 was used since the trial process for fraud cases takes a long time to get to the permanent legal power decision (inkracht). Data were analyzed using logistic regression analysis. The study results found that financial distress did not affect the probability of corruption. In contrast, regional independence positively affected the likelihood of corruption in the local governments, in Indonesia. If regional independence is high, then the probability of corruption in the local government is also high, and vice versa. The study findings were also robust in an independent analysis when the additional test was carried out. Empirically, this study found that the independence of funding sources, independence ratios to meet regional needs, and regional income could be used to detect corruption in Indonesian local governments. While the budget solvency ratio, financial performance ratio of budget, the financial performance ratio of fund equity, and regional financial efficiency could not. The pressure to commit corruption occurs because the region is in an independent state. Therefore, supervision of the implementation of fiscal decentralization needs to be done so that corruption does not happen.